High-frequency induction of multiple shoots and plant regeneration from cotyledonary node explants of Tongkat Ali (Eurycoma Longifolia Jack) - Alttaher, Annor Gebril Annour; Balia Yusof, Zetty Norhana; Mahmood, Mahmmod Basher; Shaharuddin, Noor Azmi (Applied Ecological Research and Forensic Institute, 2020)
Eurycoma longifolia Jack is traditionally used as an aphrodisiac and health supplement for various diseases. Due to its potential commercial value as a plantation crop as well as to conserve its germplasm, it is necessary to establish a suitable protocol of propagation as a better alternative for mass production. Hence, this study describes an efficient and reproducible in vitro regeneration system of E. longifolia. Cotyledonary node explants were excised from 2-week-old in vitro seedlings and cultured on Murashige and Skoog (MS) medium supplemented with different concentrations of 6-benzyl aminopurine (BAP), kinetin (KIN) and thidiazuron (TDZ). In addition, various concentrations of indole-3-butyric acid (IBA) and α- naphthaleneacetic acid (NAA) were tested for in vitro rooting of shoots. From the results, it was observed that 1.0 mgL-1 of BAP induced the highest percentage of shoot formation (76.7%) from cotyledonary node explants. The best rooting response was observed on half-strength MS medium containing 0.5 mgL-1 IBA with an average of 3.2 roots per shoot. Regenerated plantlets were successfully acclimatized to ex vitro conditions with an 85% survival rate. Overall, this in vitro regeneration protocol provides a rapid technique that can be utilized for commercial propagation and genetic transformation of this medicinal plant.